Debt finance as a public phenomenon: conceptual basics and prospects of democratization - Kyrylenko, Olha; Derlytsia, Andrii (Herald of Economics, 2019)
Introduction. Issues of budget deficits, public credit and debt form the sphere of debt finance – a model established in a particular country for ensuring the balance of the budget, the organization of government borrowings, the system of public debt management in order to influence the development of the economy and the functioning of public finance.Methods. The methods of abstraction, comparison, institutional analysis and idealization have been used.Results. The study draws attention to the microeconomic fundamentals of debt finance, considering them through the prism of the individual interests. It has been found out that the developed Western countries are characterized by the public nature of debt finances as a result of the evolutionary democratization of public debt – the accessibility of government debt operations to the general public. It is revealed that due to a number of institutional restrictions, the democratization of this sphere in Ukraine has not been fully implemented yet. It is proved that the public debt manifests the same power as pure public goods: the indivisibility in consumption and the impossibility to exclude from the debt burden, which enable its study as public bads. The key features that determine the social nature of debt finance in developed democratic countries are revealed. It is proved that the determinants of debt finance are both economic and political and institutional imbalances, not only in the area of public finance, but also at the level of economic entities. The key components of the institutional environment of the functioning of debt finance are considered: political decision- making mechanisms, procedures of the budget process, the institutional organization of the financial market. It is argued that one of the key shortcomings of the domestic practice of servicing domestic public debt is the insignificant share of debt owned by citizens.Conclusions. The disadvantages and obstacles of democratization of the model of borrowing in Ukraine are studied in the paper. A promising mechanism of financial inclusion of the population in transactions with government debt is proposed.